2013
DOI: 10.1021/jo400440z
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward Access to Spisulosine and 4,5-Dehydrospisulosine Stereoisomers: Probes for Profiling Ceramide Synthase Activities in Intact Cells

Abstract: A stereoselective synthesis of spisulosine (ES285) and 4,5-dehydrospisulosine stereoisomers is described. Hydrozirconation of 1-pentadecyne with Schwartz reagent, followed by diastereocontrolled addition to L- or D-alaninal afforded the required 2-amino-1,3-diol framework. The resulting sphingoid bases revealed as excellent probes for the profiling of ceramide synthase activity in intact cells. Among the sphingoid bases described in this work, spisulosine (ES285), RBM1-77, and RBM1-73 were the most suitable on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…The reaction rendered the acylated product ( R , R )‐ 14 in 39 % yield and 85 % ee , whereas the starting material was recovered in 40 % yield and 61 % ee , with an s ‐factor of 23. The absolute configuration of compound ( S , S )‐ 13 was assigned by comparison of the HPLC traces with the same product prepared from Garner's aldehyde by applying a stereospecific synthetic route (see the Supporting Information) . These results confirmed that the configuration of the carbon atom with the amino function determined the enantiomer being acylated, for a specific enantiomer of a catalyst, whereas the adjacent stereocentre had little influence on the final outcome of the KR process.…”
Section: Resultsmentioning
confidence: 72%
“…The reaction rendered the acylated product ( R , R )‐ 14 in 39 % yield and 85 % ee , whereas the starting material was recovered in 40 % yield and 61 % ee , with an s ‐factor of 23. The absolute configuration of compound ( S , S )‐ 13 was assigned by comparison of the HPLC traces with the same product prepared from Garner's aldehyde by applying a stereospecific synthetic route (see the Supporting Information) . These results confirmed that the configuration of the carbon atom with the amino function determined the enantiomer being acylated, for a specific enantiomer of a catalyst, whereas the adjacent stereocentre had little influence on the final outcome of the KR process.…”
Section: Resultsmentioning
confidence: 72%
“…The 1-deoxysphinganine (1-deoxySA), which is formed by SPT through the condensation of palmitoyl-CoA and alanine, is N-acylated to 1-deoxy-dihydroceramides (5,16,17). However, while canonical dihydroceramides are converted to ceramides by the introduction of a 4,5 trans double bond (DB) (18,19), a 14,15 cis DB is most commonly introduced in 1-deoxy-dihydroceramides (20), indicating that 1-deoxySLs follow a different metabolic route than canonical SLs.…”
Section: Extraction and Analysis Of Sphingoid And Deoxysphingoid Basesmentioning
confidence: 99%
“…The nucleophilic addition of zirconocene compounds to aldehydes was reported by Delgado and co‐workers. This stereoselective method was used in the first step of the total synthesis of Spisulosine ( 117 ) and 4,5‐dehydrospisulosine ( 118 ) (Scheme ) . The hydrozirconation of 1‐pentadecyne ( 113 ) with Schwartz's reagent followed by the addition into N ‐Boc‐ l ‐alaninal, afforded the desired sphingoid base ( 116 ) as a mixture of diastereomers.…”
Section: Addition Of Organozirconium Species Into Imines and Aldehydesmentioning
confidence: 99%